ROLE OF HOMOEOPATHIC SARCODE FOLLICULINUM IN 200 POTENCY IN CASES OF AMENORRHOEA -A CASE SERIES - Dr. Jayshree Rathva; Dr. Tarun Kumar Das (The Bioscan, 2025)
Background: Amenorrhea is a common gynecological complaint affecting women of reproductive age, with significant implications on their physical and psychological health. Conventional treatment often focuses on hormonal regulation, while homoeopathy provides individualized remedies based on symptom similarity. Folliculinum, a remedy prepared from ovarian follicle, has been clinically observed to play a role in regulating menstrual dysfunctions. Objective: To evaluate the effect of Folliculinum 200C potency in cases of amenorrhea and assess its potential in restoring normal menstrual function. Method: A case series of five patients presenting with amenorrhea was conducted. Detailed case histories were taken, and prescriptions were made on the therapeutic indication of Folliculinum 200C. Patients were followed up regularly over a period of three months, and clinical response was documented. Parameters assessed included onset of menstruation, regularity of cycles, and associated symptoms. Result: All five patients exhibited significant clinical improvement following administration of Folliculinum 200C. Restoration of normal menstrual cycles was achieved within three months of treatment. Improvement was also noted in associated complaints such as fatigue, mood disturbances, and hormonal imbalance symptoms. No adverse effects were reported during the follow-up period. Conclusion: The results of this case series suggest that Folliculinum 200C may be a useful homoeopathic remedy in the management of amenorrhea. The positive outcomes observed warrant further clinical research with larger sample sizes and controlled studies to substantiate the role of Folliculinum in menstrual disorders.